Investigation of suitable conditions for the growth and producing biofilm of denitrifying bacteria - Hà, Hoàng Phương; Huy, Nguyễn Quang; Yến, Hoàng Thị (Vietnam Journal of Biotechnology, 2016)
Denitrification occurs under anaerobic conditions, utilizing organic substances such as a carbon source and nitrate as the terminal electron acceptor. Some bacteria strains that are capable of producing biofilm and are attached to the carrier for the applications of the nitrate contaminated water treatment. This process is done simultaneously with the process of nitrification, nitrifying bacteria on the biofilm surface (ocic zone), denitrifying bacteria under biofilm (anoxic zone). The selection of suitable conditions for the growth and production of biofilm of denitrifying bacteria is the target of this research. Two strains D10 and D32 are capable to reduce nitrate and created the best biofilm. Optimal conditions for the strain growth were: 37oC, pH 6.6 - 7. Supplementation of 0.006% M1, E2 (methanol, ethanol) increased the reducing N-NO3 to 80% and 100% respectively. Denitrification process still occured in aerobic condition but with lower efficiency (25.8%) byD32 strain. Based on 16S rRNA gene analysis, D10 strain was the closest relative with Bacillus fusiformis, D32 closest to Pseudomonas denitrifricans.